Novel food preservation and microbial assessment techniques [ - Boziaris, Ioannis S. (CRC Press, 2014)
"The introduction of microbial ecology and ?hurdle theory? concepts in food microbiology during late 1980?s contributed greatly to its evolution, while the improvement of microbiological methods offered useful tools for monitoring microbiological quality and safety of foods. Subsequently, the demand for minimal processing promoted the development of innovative non-thermal techniques and application of mild preservation strategies for microbial control in foods. Additionally, the application of molecular genetic methods, offered a powerful tool for better exploration and understanding of food microbial diversity. The aim of this book is a thorough presentation of the recent and novel advances in food microbiology. The book is divided in two parts. The fi rst part discusses the microbiology of novel food preservation methods. Some of those methods have already numerous applications, such as high pressure processing, while others appear to be very promising for future applications. The second part is dedicated on the newly developed applications of molecular genetics and instrumental analysis for detection and monitoring of microorganisms and their activity in food systems. Non-thermal processing has a lot of advantages compared to tradition heat processing. Chapter 1 discusses the high pressure processing (HHP), a non-thermal preservation technique for producing high quality food with minimal changes in colour, fl avour and texture, when compared with conventional thermal processing. Additionally, the predictive modeling of HHP induced microbial inactivation and the phenomena of injured-recovery of microbial cells after HHP-treatment are also included"-- Provided by publisher